Autonomic Nervous System Dysfunction Is Associated With Re-hospitalization in Pediatric Septic Shock Survivors - Badke, Colleen M.; Swigart, Lindsey; Carroll, Michael S.; Weese-Mayer, Debra E.; Sanchez-Pinto, L. Nelson (Frontiers in Pediatrics, 2022)
Objective: Re-hospitalization after sepsis can lead to impaired quality of life. Predictors of re-hospitalization could help identify sepsis survivors who may benefit from targeted interventions. Our goal was to determine whether low heart rate variability (HRV), a measure of autonomic nervous system dysfunction, is associated with re-hospitalization in pediatric septic shock survivors. Materials and Methods: This was a retrospective, observational cohort study of patients admitted between 6/2012 and 10/2020 at a single institution. Patients admitted to the pediatric intensive care unit with septic shock who had continuous heart rate data available from the bedside monitors and survived their hospitalization were included. HRV was measured using age-normalized z-scores of the integer HRV (HRVi), which is the standard deviation of the heart rate sampled every 1 s over 5 consecutive minutes. The 24-h median HRVi was assessed on two different days: the last 24 h of PICU admission (“last HRVi”) and the 24-h period with the lowest median HRVi (“lowest HRVi”). The change between the lowest and last HRVi was termed “delta HRVi.” The primary outcome was re-hospitalization within 1 year of discharge, including both emergency department encounters and hospital readmission, with sensitivity analyses at 30 and 90 days. Kruskal-Wallis, logistic regression, and Poisson regression evaluated the association between HRVi and re-hospitalizations and adjusted for potential confounders. Results: Of the 463 patients who met inclusion criteria, 306 (66%) were re-hospitalized, including 270 readmissions (58%). The last HRVi was significantly lower among re-hospitalized patients compared to those who were not (p = 0.02). There was no difference in the lowest HRVi, but patients who were re-hospitalized showed a smaller recovery in their delta HRVi compared to those who were not re-hospitalized (p = 0.02). This association remained significant after adjusting for potential confounders. In the sensitivity analysis, a smaller recovery in delta HRVi was consistently associated with a higher likelihood of re-hospitalization. Conclusion: In pediatric septic shock survivors, a smaller recovery in HRV during the index admission is significantly associated with re-hospitalization. This continuous physiologic measure could potentially be used as a predictor of patients at risk for re-hospitalization and lower health-related quality of life.